2002
DOI: 10.1007/s11926-002-0057-2
|View full text |Cite
|
Sign up to set email alerts
|

Advances in the understanding of entheseal inflammation

Abstract: The importance of enthesitis in the pathogenesis of spondyloarthropathy (SpA) is now well recognized. Several entheses comprise more than simply the insertion site, and they are part of a complex biomechanical organ to resist shear and compression. It is also evident that tendons that wrap around bony pulleys form an integral part of joint capsules, and share, along with imaging abnormalities and histopathologic changes, common anatomic, histologic, and biomechanical features with classically defined entheses.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
24
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 59 publications
(25 citation statements)
references
References 30 publications
1
24
0
Order By: Relevance
“…We have previously shown that HLA-B27 determines the severity of osteitis adjacent to the plantar fascia in early SpA 20 29. This study confirms these observations at the SIJ and is in accordance with other reports also in early disease 30.…”
Section: Discussionsupporting
confidence: 93%
“…We have previously shown that HLA-B27 determines the severity of osteitis adjacent to the plantar fascia in early SpA 20 29. This study confirms these observations at the SIJ and is in accordance with other reports also in early disease 30.…”
Section: Discussionsupporting
confidence: 93%
“…Some MRI studies have demonstrated a clear link between enthesitis and synovitis in individual swollen joints in PsA, but not in RA 5 12. Following this line, McGonagle et al developed the concept of the ‘enthesis organ’,13 which comprises the enthesis and also adjacent fibrocartilages and synovial membranes. Although enthesitis is typically viewed as a focal insertional disorder, MRI and US findings have demonstrated the presence of more diffuse inflammatory changes involving areas distant from the insertion sites 14 15.…”
Section: Discussionmentioning
confidence: 99%
“…Enthesitis may be associated with adjacent osteitis detectable by magnetic resonance imaging. 41 Skin and nail involvement Keratoderma blenorrhagica affects 5%-10% of patients and is highly characteristic of reactive arthritis. Histologically, appearances are identical to pustular psoriasis.…”
Section: Musculoskeletal Manifestationsmentioning
confidence: 99%